MUHAMMAD ABDUH’S INFLUENCE ON AL-WAQĀI’ AL-MIṢRIYYAH: SHAPING EGYPT’S OFFICIAL GAZETTE - Ahmad Nabil Amir; Tasnim Abdul Rahman (UIN Raden Mas Said Surakarta, 2024)
This research aims to discuss the role of Muhammad Abduh (1849-1905) as the leading editor of al-Waqāi‘ al-Miṣrīyyah (Egyptian Events), an official Egyptian gazette. His editorial work has had a profound impact on its progress in the context of the rising popularity of al-Waqāi‘ al-Miṣrīyyah during his editorship (1880-1882), establishing its reputation as a leading Egyptian newspapers. This study contributes to illuminating Abduh’s column and writing that was instrumental in highlighting unprecedented socio-cultural and religious reform undertaken by the government, amid phenomenal and competitive growth of independent press and helped to develop a national consciousness of modernizing programs and influencing public opinion in Egypt. It allowed for better development of formidable national spirit and mainstreaming of their common ideal and convention in language, literature and culture as well as mobilizing social awareness of intense political and cultural dynamics in the Egyptian heartland. His career spanned the period of Riyad Pasha and Sharif’s administration and subsequent political unrest. The research is based on qualitative and documentation techniques. It reviewed accumulated data by way of descriptive, analytical, historical and comparative methods. The main finding delineates that al-Waqāi‘ has assumed unprecedented influence and success during his editorship through his dynamic and productive articles and rigorous daily basis of production of the newspaper that helps to raise public issues and concern and attract awareness of global political current as well as defending the significance value, norms and ethics of journalism.